Lux light in the library - Yiau, Tee Lee; Yeoh, Kai Zhe; Chew, Ge Yin; Ngui, Yi Tung; Yew, Zhi En; Ashley Yoong, Yu Xuan (Universiti Teknologi MARA, Kedah, 2019)
The LUX Light in the Library is help the students to locate the books easily. We can save to search for the books. We use a computer program to control the sensors that are connected to the LED bulb on the rack. When the librarians search for the books an actual floor plan with directions will be displayed on the system and the LED bulb on the rack will be lit up to indicate the location of the books. With this system it will enhance the efficiency of locating books. We hope that we able to bring our idea to the society and library world. We hope that we can contribute our ideas to the world.